Making rules credible: Divided government and political budget cycles - Jorge M. Streb; Gustavo F. Torrens (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2009)
Political budget cycles (PBCs) result from the credibility problems that office-motivated incumbents face under asymmetric information, due to their temptation to manipulate fiscal policy to increase their electoral chances. We analyze the role of rules that limit debt, crucial for aggregate PBCs to take place. Since the budget process under separation of powers typically requires that the legislature authorize new debt, divided government can make these fisscal rules credible. Commitment is undermined either by unified government or by imperfect compliance with the budget law. When divided government affects efficiency, voters must trade off electoral distortions and government competence.
Keywords: 330; political budget cycles; discretion; unified government; rules; credibility; separation of powers; divided government